2017
DOI: 10.3390/md15110337
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenans-Sulfated Polysaccharides from Red Seaweeds as Matrices for the Inclusion of Echinochrome

Abstract: The possibility of using different types of carrageenans (CRG) as matrixes for incorporating of echinochrome A (Ech) was investigated. Ech interacts with carrageenans and is incorporated into the macromolecular structure of the polysaccharide. The inclusion of Ech in carrageenan matrices decreased its oxidative degradation and improved its solubility. The changing in the charge and morphology of CRGs during binding with Ech was observed. The rate of Ech release from CRG matrices depended on the structure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 41 publications
(53 reference statements)
2
20
0
Order By: Relevance
“…We tried to incorporate Ech in phosphate buffer into liposomes, but in this case, the Ech oxidized rapidly and the obtained liposomes contained a non-native, but oxidized form of Ech. According to our earlier results, CRGs protected the Ech from its oxidative degradation and improved its solubility [ 27 ]. So it was not possible to incorporate the Ech without carrageenan into the liposomes.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…We tried to incorporate Ech in phosphate buffer into liposomes, but in this case, the Ech oxidized rapidly and the obtained liposomes contained a non-native, but oxidized form of Ech. According to our earlier results, CRGs protected the Ech from its oxidative degradation and improved its solubility [ 27 ]. So it was not possible to incorporate the Ech without carrageenan into the liposomes.…”
Section: Resultsmentioning
confidence: 94%
“…The red pigment of water-insoluble Ech from sea urchins is the active substance of the drug Histochrome and exhibits high antioxidant activity [ 30 , 31 ]. Recently, we have shown that the incorporation of Ech into the CRG matrix improves its water solubility and prevents Ech from oxidation [ 27 ]. In the present work, we included CRG/Eсh in the liposomes and examined the properties of these liposomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations